(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To determine experimentally the threshold voltage for retinal high-frequency electric welding (HFEW) using a 25-gauge original unipolar welding probe depending on the content of the vitreous cavity and justify the results theoretically by finite element modeling (FEM). Material and Methods: The experiment involved three rabbits (6 eyes; two experimental rabbits and one control rabbit). Retinal HFEW was performed in eyes filled with perfluorodecalin (PFD) or air in the experimental group and intact vitreous body in the control group. FEM was used for simulating the effects of retinal heating with electric current. Results: In the experimental study, the threshold voltage for retinal HFEW was 11 V, 12 V and 12 V in the presence of the vitreous, PFD and air, respectively. Findings of the FEM of the electric current flow through the tissue (10.8 V for the vitreous, 11.5 V for the air and 12 V for PFD) confirmed the experimental results. Other HFEW settings (current frequency, 66 kHz; current, 0.3A; exposure duration, 1 s) were not changed throughout the experiment. The difference in the threshold voltage for HFEW of the retina can be explained by a relatively high conductivity of the vitreous, while PFD and air are dielectrics. Conclusion: The threshold voltage for retinal HFEW using a 25-gauge original unipolar welding probe was 11 V, 12 V and 12 V in the presence of the vitreous, air and PFD in the vitreous cavity, respectively, which was confirmed by FEM simulations.